2019
DOI: 10.1055/s-0037-1611788
|View full text |Cite
|
Sign up to set email alerts
|

Hitchhiker’s Guide to Reductive Amination

Abstract: A comparative study of various widely used methods of reductive amination is reported. Specifically, such reducing agents as H2, Pd/C, hydride reagents [NaBH4, NaBH3CN, NaBH(OAc)3], and CO/Rh2(OAc)4 system were considered. For understanding the selectivity and activity of the reducing agents reviewed herein, different classes of starting materials were tested, including aliphatic and aromatic amines, as well as aliphatic and aromatic aldehydes and ketones. Most important advantages and drawbacks of the methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 35 publications
0
76
0
Order By: Relevance
“…The use of carbon monoxide proved to be effective in reductive alkylation, amination, and esterification reactions of carbonyl compounds. The key advantage of this reducing agent is the lack of external hydrogen source, which leads to unique selectivity often surpassing more traditional, hydride‐based reducing agents . Previously, we developed a method for reductive amidation with carbon monoxide as the reducing agent using homogeneous rhodium and ruthenium catalysts .…”
Section: Catalysts Screeningmentioning
confidence: 99%
“…The use of carbon monoxide proved to be effective in reductive alkylation, amination, and esterification reactions of carbonyl compounds. The key advantage of this reducing agent is the lack of external hydrogen source, which leads to unique selectivity often surpassing more traditional, hydride‐based reducing agents . Previously, we developed a method for reductive amidation with carbon monoxide as the reducing agent using homogeneous rhodium and ruthenium catalysts .…”
Section: Catalysts Screeningmentioning
confidence: 99%
“…An experimental comparative study for the most popular reducing agents has been recently published. [ 162 ] Here we discuss applications of this approach in the tertiary amines synthesis.…”
Section: Trialkylamines Synthesismentioning
confidence: 99%
“…Standard protocols for the synthesis of tertiary amines from aldehydes and ammonium salts often require the use of borohydride reductants or excess of other reducing agents to effectively conduct the reaction. [14k] In our previous research we have shown that carbon monoxide can be potentially one of the most selective and atom‐economical alternatives to the classical reductants in this process …”
Section: Introductionmentioning
confidence: 99%
“…[14k] In our previous research we have shown that carbon monoxide can be potentially one of the most selective and atom-economical alternatives to the classical reductants in this process. [17] We have also recently reported a novel method for the synthesis of symmetrical tertiary amines from aldehydes without an external hydrogen source. [18] The amine source in this reaction is acetamide.…”
Section: Introductionmentioning
confidence: 99%